2008
DOI: 10.1002/jez.463
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory effects of starvation on prothoracic gland cell DNA synthesis during the last larval instar of the silkworm, Bombyx mori

Abstract: Activation of DNA synthesis in prothoracic gland cells of the silkworm, Bombyx mori, during the middle stages of the last larval instar appears to be nutrition dependent, with starvation on day 3 of the last larval instar inhibiting its dramatic increase. The possible cellular mechanism causing the inhibition of DNA synthesis owing to starvation was further examined by determining changes in the growth-promoting activity of the hemolymph and the responsiveness of gland cells to starvation. The results showed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 33 publications
(22 reference statements)
0
1
0
Order By: Relevance
“…These findings suggest that the degree of DNA synthesis in the silk gland may be related to the feeding rate during the intermolt stages. The DNA synthesis of prothoracic gland cells was also inhibited by starvation, which suggests that the inhibition of DNA synthesis may be related to changes in growth factor receptors and downstream signaling within the tissues (Chen & Gu, ). It has been shown that most endoreplicative cells proliferate in a nutrition‐dependent manner in Drosophila melanogaster (Britton & Edgar, ).…”
Section: Discussionmentioning
confidence: 99%
“…These findings suggest that the degree of DNA synthesis in the silk gland may be related to the feeding rate during the intermolt stages. The DNA synthesis of prothoracic gland cells was also inhibited by starvation, which suggests that the inhibition of DNA synthesis may be related to changes in growth factor receptors and downstream signaling within the tissues (Chen & Gu, ). It has been shown that most endoreplicative cells proliferate in a nutrition‐dependent manner in Drosophila melanogaster (Britton & Edgar, ).…”
Section: Discussionmentioning
confidence: 99%